2008
DOI: 10.1111/j.1462-5822.2008.01158.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis ofEntamoeba histolyticatowards the pro-inflammatory cytokine TNF is based on PI3K signalling, cytoskeleton reorganization and the GalactoseN-acetylgalactosamine lectin activity

Abstract: SummaryEntamoeba histolytica is the protozoan parasite responsible for human amoebiasis. During invasive amoebiasis, migration is an essential process and it has previously been shown that the pro-inflammatory compound tumour necrosis factor (TNF) is produced and that it has a migratory effect on E. histolytica. This paper focuses on the analysis of parasite signalling and cytoskeleton changes leading to directional motility. TNF-induced signalling was PI3K-dependent and could lead to modifications in the pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…It has been shown that TNF-␣ has a chemotactic effect on E. histolytica; hence, it is possible that by enhancing TNF-␣, EhMIF promotes parasite invasion (57,58). Also, TNF-␣ promotes adherence of E. histolytica to host cells (59).…”
Section: Fig 3 Ehmif Immunomodulates Macrophages (A)mentioning
confidence: 99%
“…It has been shown that TNF-␣ has a chemotactic effect on E. histolytica; hence, it is possible that by enhancing TNF-␣, EhMIF promotes parasite invasion (57,58). Also, TNF-␣ promotes adherence of E. histolytica to host cells (59).…”
Section: Fig 3 Ehmif Immunomodulates Macrophages (A)mentioning
confidence: 99%
“…Only a few cell surface-initiated, ligand-induced signaling pathways have been documented, examples being the initiation of phagocytosis [32,33], chemotactic response [34], and fibronectin-induced cytoskeleton reorganization [35]. Although several putative cell-surface receptors, such as a 170 kDa Gal/GalNAc lectin (a laminin receptor) and LECAM3 (a homolog of the leukocyte adhesion molecule) have been identified, signaling pathways that function via these molecules have not yet been elucidated [36].…”
Section: Pathogenesis: Role Of Signaling Pathwaysmentioning
confidence: 99%
“…Motile responses of Entamoebahistolytica trophozoites to specific stimuli are important factors not only for their survival in the human intestine as commensals, but also for their activities as invasive pathogens [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%